1981
DOI: 10.1037/0022-3514.40.3.441
|View full text |Cite
|
Sign up to set email alerts
|

Person categories and social perception: Testing some boundaries of the processing effect of prior knowledge.

Abstract: Current assumptions about the processing role of prior social knowledge in social perception may need modification when applied to situations that are richer and more complex than typical research paradigms. Two experiments investigated whether stereotypic knowledge would influence social perception in a more realistic setting. In Experiment 1, subjects watched a videotape of a target woman identified either as a waitress or a librarian. Subjects more accurately rememA bered features of the woman that were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
186
0
6

Year Published

1985
1985
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(204 citation statements)
references
References 21 publications
12
186
0
6
Order By: Relevance
“…This means that information processing on both the individual and organizational level is influenced by prior experiences. Knowledge structures allocate attention (White and Carlston 1983), enable encoding (Cohen 1981), retrieval from memory (Anderson and Pichert 1978;Cantor and Mischel 1977), and help interpret experiences (Bower et al 1979) (for details, please see Walsh 1995). Pursuant to organizational learning theory, learning effects are influenced by cognitive patterns, among other things, determining perceptions and conclusions, as well as by the similarity of antecedent situations (Haleblian and Finkelstein 1999).…”
Section: Strategic Consistencymentioning
confidence: 99%
“…This means that information processing on both the individual and organizational level is influenced by prior experiences. Knowledge structures allocate attention (White and Carlston 1983), enable encoding (Cohen 1981), retrieval from memory (Anderson and Pichert 1978;Cantor and Mischel 1977), and help interpret experiences (Bower et al 1979) (for details, please see Walsh 1995). Pursuant to organizational learning theory, learning effects are influenced by cognitive patterns, among other things, determining perceptions and conclusions, as well as by the similarity of antecedent situations (Haleblian and Finkelstein 1999).…”
Section: Strategic Consistencymentioning
confidence: 99%
“…The bias component of social judgment has gained importance over the years. At first, it was viewed as response error that should be corrected in order to better estimate "true" social judgments (e.g., Cohen, 1981;Hartwick, 1979); next, it came to be recognized as an important side-effect of the normal use of cognitive schemas (e.g., W. Brewer & Nakamura, 1984;Rumelhart, 1984); and most recently, the bias component is considered the implicit process constituent of dual-process approaches (Chaiken & Trope, 1999). It is important to note that although work in several areas of social cognition assumes the operation of both heuristic and systematic processes, until recently there was little in the way of independent assessment of these two processes as aspects of social cognition.…”
Section: Automatic and Controlled Influences In Social Judgmentsmentioning
confidence: 99%
“…Apart from providing information about the contents and structure of cognitive categories, these studies have shown that the cognitive organization of social stimuli in terms of prototypes facilitates information-processing, such as faster and better recall for prototype-consistent as opposed to inconsistent information (e.g. Cohen, 1981).…”
mentioning
confidence: 99%